Fundamental features of social environments determine rate of social affiliation - Sankalp Garud; Miruna Rascu; Sorcha Hamilton; Ingrid Yu; Matthew F. S. Rushworth; Miriam C. Klein-Flügge (Proceedings of the National Academy of Sciences, 2025)
Humans start new friendships and social connections throughout their lives and such relationships foster mental and physical well-being. While friendship initiation may depend on alignment of subtle and complex personal variables, here we investigated whether it also depends on basic features of social environments. In a preregistered online study (n = 783) using a novel social-affiliation seeking paradigm, we found people were more likely to send friend requests as the density of friendship opportunities decreased and frequency of success increased. Further, we found task-related measures, like overall friend requests, were correlated with mental health dimensions like social thriving and anhedonia. Next, in an ultra-high-field fMRI study (n = 24), we found that both fundamental features of social environments--opportunity density and frequency of success--affected neural activity across a network of regions linked to foraging including dorsal raphe nucleus, substantia nigra, and anterior insula. Thus, humans consider the background statistics of an environment while making social decisions and these decisions are linked to activity in cortico-subcortical circuits mediating the influence of environmental statistics on other aspects of behavior. Moreover, individual differences in how environmental features influence social behavior are associated with variation in mental health dimensions, offering key insights into interindividual variability in social functioning.